Do goats recognise humans cross-modally? - Marianne A. Mason; Stuart Semple; Harry H. Marshall; Alan G. McElligott (PeerJ)
Recognition plays a key role in the social lives of gregarious species, enabling animals to distinguish among social partners and tailor their behaviour accordingly. As domesticated animals regularly interact with humans, as well as members of their own species, we might expect mechanisms used to discriminate between conspecifics to also apply to humans. Given that goats can combine visual and vocal cues to recognise one another, we investigated whether this cross-modal recognition extends to discriminating among familiar humans. We presented 26 goats (17 males and nine females) with facial photographs of familiar people and two repeated playbacks of a voice, either congruent (from the same person) or incongruent with that photograph (from a different person). When cues were incongruent, violating their expectations, we expected goats to show changes in physiological parameters and moreover, respond faster and for longer after playbacks. Accordingly, heart rate decreased as the playback sequence progressed, but only when the face and voice presented were incongruent. Heart rate variability was also affected by congruency, but we were unable to determine precisely where differences lay. However, goats showed no changes in time taken to respond, or how long they responded for (our primary variables of interest). We also found evidence to suggest that shifts in cardiac responses may not have been robust. Although our findings could imply that goats had successfully perceived differences in congruency between the visual and vocal identity information presented, further evidence is needed to determine whether they are capable of cross-modal recognition of humans.